The saving and employment effects of higher job loss risk - Ragnar E. Juelsrud; Ella Getz Wold (Norges Bank, 2019)
In this paper we use Norwegian tax data and a novel natural experiment to isolate the impact of job loss risk on saving behavior. We find that a one percentage point increase in job loss risk increases liquid savings by roughly 1.2 - 2.0 percent. Further, we show that employment falls in non-tradable industries not directly affected by the shock, also after controlling for intersectoral linkages and lower demand from affected industries, consistent with the household demand channel of recessions.
hdl:11250/2652985
Keywords: D14; E20; E21; 330; Precautionary savings; household finance; recessions